Ciencia e investigación agraria 2019
DOI: 10.7764/rcia.v46i2.2151
|View full text |Cite
|
Sign up to set email alerts
|

Quinoa (Chenopodium quinoa Willd.) crop under Mediterranean conditions: a review

Abstract: D.J. Bilalis, I. Roussis, I. Kakabouki, and A. Folina. 2019. Quinoa (Chenopodium quinoa Willd.) crop under Mediterranean conditions: a review. Cien. Inv. Agr. 46(2): 51-68.Quinoa is a pseudocereal crop that is well adapted to a wide range of climatic conditions and has significant potential for increased production as a new crop in the Mediterranean region and in other parts of the world, including northern Europe, North America, Asia, and Africa. Because of its exceptional nutritional properties, quinoa is hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 70 publications
1
12
1
Order By: Relevance
“…During the first annuity (2017), a decrease in yield (1.5 t/ha) compared to 2018 (2.5 t/ha) was observed. Moreover, the two-year average yield (2.0 t/ha) was slightly lower than those previously reported for quinoa under Mediterranean field conditions in which yields did not vary between years (Bilalis et al, 2019;Pulvento, 2015).…”
Section: Discussioncontrasting
confidence: 65%
“…During the first annuity (2017), a decrease in yield (1.5 t/ha) compared to 2018 (2.5 t/ha) was observed. Moreover, the two-year average yield (2.0 t/ha) was slightly lower than those previously reported for quinoa under Mediterranean field conditions in which yields did not vary between years (Bilalis et al, 2019;Pulvento, 2015).…”
Section: Discussioncontrasting
confidence: 65%
“…Particularly in Europe, there is a great interest in growing quinoa ( 27 ). In fact, it was introduced in northern European countries (i.e., England, Denmark, and Netherlands) in the late 1970s and early 1980s, and nowadays, it is also cultivated in the Mediterranean region ( 28 ). In Spain, quinoa has spread significantly in recent years, particularly in the southern part of the country ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, quinoa was introduced in the early 2000s thanks to several research projects dealing with the adaptation of this species to the peninsula agricultural system [ 15 , 16 , 17 ]. Results indicated that, given its high resiliency and tolerance to abiotic stresses, in particular salinity and drought, quinoa could represent a good alternative to the traditional Mediterranean crops in light of the current climate change [ 18 ].…”
Section: Introductionmentioning
confidence: 99%